Effect of intercritical annealing on the microstructural and mechanical behaviours of dual-phase steels - Nora Osman; Zainuddin Sajuri; Intan Fadhlina Mohamed; Mohd Zaidi Omar; Syarif Junaidi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The automotive industry is the main consumer of dual-phase (DP) steels which have relatively impressive mechanical strength. DP steels are also known to have good ductility and load-bearing property because of their hard martensitic microstructure in soft ferrite grains. The main objective of this study is to determine the mechanical behaviour of DP steels with various martensite volume fractions. A heat treatment with an intermediate quenching procedure followed by three different intercritical temperatures is conducted to produce various ferrite–martensite containing DP steels with different martensite volume fractions (Vm ). Vm affects the mechanical properties of steel, such as work hardening, ultimate tensile strength, yield strength and hardness. The results of the experiments conducted in this study prove that excellent work hardening and ductility are observed for DP steels with a low amount of martensite phase. Meanwhile, DP steels with high Vm exhibit high tensile strength and hardness with low ductility. Considère criterion is used to analyse the work hardening behaviour of DP steels. Results indicate that a one-stage work hardening takes place in DP steels; according to Considère criterion, instability strain or uniform elongation is also slightly increased by decreasing the martensite volume fraction or increasing the work hardening rate.